IMPACT STREET EARNINGS ON FINANCIAL DISTRESS - Zulfikar Ikhsan Pane (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2021)
This study aims to find out correlation street earnings and financial distress of manufacturing companies in Indonesia Stock Exchange (IDX). This research using companies listed during 2010 – 2017 obtained from OSIRIS database with valid sample are 55 companies, 188 observation. Regression multivariate are use for data analysis. This result is street earnings positive significant to financial distress, means financial distress become lower when street earnings higher. Limitation of this study are only observe manufacturing company so further research could be possible to another industries.